The Role of Self Control as a Moderator Variable on the Effect of Schadenfreude on Bullying Behavior in Junior High School Students - Winggo Romadhana; Andik Matulessy; Amanda Pasca Rini (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to ascertain whether self-control is a moderator of the influence of schadenfreude on bullying behavior. Quantitative research methodology was used in this study. Students in junior high schools from all over Surabaya became the study population. Purposive sampling was used for sampling. The number of samples obtained was 366 students. Data collection was carried out using a questionnaire. The analysis technique used is the classic assumption test and path analysis. The results showed that self-control is able to mediate the effect of schandenfreud on bullying behavior, self-control with bullying behavior has a significant relationship, schandenfreud with bullying behavior has a significant relationship, and schandenfreud with self-control has a significant relationship. This study can enrich existing educational psychology theories regarding the influence of schadenfreude on the tendency of bullying behavior, and explain how self-control becomes a moderating variable in the influence of schadenfreude on bullying behavior.